Social Satire in Jane Austen’s Persuasion (Journal of the College of Basic Education, 2023)
In Persuasion, Jane Austen offers a penetrating critique of the standards of the British class system. She criticizes a system based onsocial distinctions and definitions like “Superior” and “ Inferior .” Through irony and satire, she vividly shows Victorian classrigidity and its traditional values. This paper aims at showing that through her realistic portrayal offamilies and characters; Austen manages to capture the major defects ofher social circle and sets to expose them one by one.